Adaptability and phenotypic stability of Early-Maturing Cowpea (Vigna unguiculata (L.) Walp.) lines in the Peruvian Amazon - Gonzales Vega, Rodrigo (2025)
This study evaluated the suitability of three floodplain environments near Iquitos for cowpea cultivar recommendation. It also estimated the adaptability and phenotypic stability of 12 cowpea lines evaluated in 2004 and compared the climatic conditions between 2004 and the period of 2020–2024. Field trials were conducted using a randomized complete block design with 12 treatments and two replications. Five traits were assessed: grain yield, number of pods per plant, days to flowering, days to physiological maturity, and days to harvest. Combined ANOVA revealed significant environmental effects for all traits. Analyses using Duncan’s means test, GGE biplot, and AMMI indicated that the three sites are contrasting. The Annicchiarico index, GGE biplot, and AMMI analyses identified line CAR 3010 as having superior adaptability and stability. Paired t-tests showed that the conditions in 2020-2024 were warmer and drier than those in 2004. Therefore, Muyuy, Rafael Belaunde, and San Miguel are suitable locations for testing new cowpea lines, and CAR 3010 line is recommended for inclusion in cowpea breeding programs in the Peruvian Amazon in response to ongoing climate change.